+0  
 
0
299
2
avatar

(\root(3)(x+1)-\root(3)(x))((\root(3)(x+1))^(2)+\root(3)(x+1)\root(3)(x)+(\root(3)(x))^(2))

 Oct 15, 2017

Best Answer 

 #1
avatar+7350 
+1

Is this your problem?

 

³√( x + 1 )  -  ³√( x ) )( ³√( x + 1 )2  +  ³√( x + 1 )³√( x )  +  ³√( x )2 )

 

Since         (a - b)(a2 + ab + b2)   =   a3 - b3

so does...

 

³√( x + 1 )  -  ³√( x ) )( ³√( x + 1 )2  +  ³√( x + 1 )³√( x )  +  ³√( x )2 )     =    ³√( x + 1 )3  -  ³√( x )3

 

=   x + 1  -  x   =   1

 Oct 15, 2017
 #1
avatar+7350 
+1
Best Answer

Is this your problem?

 

³√( x + 1 )  -  ³√( x ) )( ³√( x + 1 )2  +  ³√( x + 1 )³√( x )  +  ³√( x )2 )

 

Since         (a - b)(a2 + ab + b2)   =   a3 - b3

so does...

 

³√( x + 1 )  -  ³√( x ) )( ³√( x + 1 )2  +  ³√( x + 1 )³√( x )  +  ³√( x )2 )     =    ³√( x + 1 )3  -  ³√( x )3

 

=   x + 1  -  x   =   1

hectictar Oct 15, 2017
 #2
avatar+98128 
+1

Nice to recognize that it was just a difference of cubes, hectictar.......!!!

 

 

cool cool cool

 Oct 15, 2017

20 Online Users

avatar
avatar